Intelligent Decision Support Based on Integration of Fuzzy Clustering and Multi objective Optimization Problem for Non Player Character in Serious Game - I.G.P. Asto Buditjahjanto; Mochamad Hariadi; Mauridhi Heri Purnomo (IPTEK The Journal for Technology and Science, 2009)
Nowadays, decision support plays an important role in decision-making, errors in decisionmaking is able to lose the competition. Decision-making is very complicated especially when the problem is in multiobjective problem. To learn decision making through play a game is an interesting thing. Player plays a game but actually, he or she learns about how to make a decision. In this research, the objective is to make Non-Player Character (NPC) for serious game for electrical power production. This NPC is developed with 2 stages, the first stage is multiobjective optimization problem that uses NSGA2 method. This stage results some optimal solutions. The second stage is clustering that uses FCM method and FLVQ method to decrease number of solutions. In this stage, we compare these methods.